Function of Trust in Building Social Solidarity in the Community Fishermen - Anwar, Sakaria; Angraeni, Retno; Djamal, Karlina (Universitas Negeri Semarang, 2020)
One of the elements of social capital existence in society is the presence of confidence (trust). Trust has a very important practical value. It is a major lubricant for the smooth working of a social system. This study aims to see how the implementation of confidence (trust) element in the community of Kuri 'Ca'Di hamlet, Nisombalia Maros Baru village. The study lasted for two (2) months using a research method that combined two instruments, which were questionnaires and interview guidelines (mix method). Data were gathered through in-depth interviews with four informants, later corroborated by data extracted quantitatively by random techniques (simple random sampling) on 40 respondents. The results showed that the community of Kuri Ca'Di had a strong bond of trust or in this case referred to the high-trust between the community members. This was evidenced by the attitude of people who easily gave aid in the form of manpower and material that was based on trust (trust). The high sense of trust led to the birth of strong solidarity among the community members so as to create a harmonious relationship and avoid the feeling of mutual distrust. Environmental security grew out of a sense of trust between the residents.